Scientific evidence of the hydrological impacts of nature-based solutions at the catchment scale - Lalonde, M.; Drenkhan, F.; Rau, P.; Baiker, J.R.; Buytaert, W. (John Wiley and Sons, 2024)
The introduction of nature-based solutions (NbS) in catchments has the potential to increase the cost-effectiveness, flexibility, and reliability of water management practices aimed at improving water security. However, the scientific-evidence base of the hydrological impacts of NbS is still weak, and there is therefore a risk that catchment interventions might not lead to the desired hydrological outcomes. This is especially important when assessing NbS-based catchment interventions before their implementation, as this requires robust simulation tools capable of effectively managing the uncertainties associated with future forecasts. This study aims to review the hydrological impacts of different NbS intervention types for water management. First, we present an NbS typology and the corresponding dominant hydrological impacts. We then use this typology to review the strength of the current evidence of the effect of NbS interventions on the hydrological response at the catchment-scale. Our results demonstrate that the effectiveness of each NbS type hinges on specific conditions such as location, design, and environmental factors. For instance, micro-reservoirs notably enhance surface storage and evaporation, while infiltration trenches reduce runoff but can increase soil erosion. Our global analysis highlights the need for an improved understanding of NbS catchment impacts and careful planning of NbS interventions as a key for successful long-term implementation of NbS. These include participatory approaches with stakeholder involvement in NbS co-design, knowledge co-production, and novel data collection to support locally relevant adaptation strategies, and to increase water security on the long term.
Keywords: Scale (ratio); Drainage basin; Environmental science; Hydrology (agriculture); Water resource management; Geography; Geology; Cartography; Geotechnical engineering; https://purl.org/pe-repo/ocde/ford#1.05.05